2014
DOI: 10.1039/c4cc01481b
|View full text |Cite
|
Sign up to set email alerts
|

Room-temperature Cu(ii)-catalyzed aromatic C–H azidation for the synthesis of ortho-azido anilines with excellent regioselectivity

Abstract: Cu(ii)-catalyzed aromatic C-H azidation with azido-benziodoxolone under mild conditions has been described. The primary amine exhibits an excellent ortho-directing effect, providing ortho-azidated anilines as the sole products.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(43 citation statements)
references
References 37 publications
0
41
0
2
Order By: Relevance
“…[34b] In 2014, two research groups reported the combination of copper catalysis with benziodoxolone 9 for the azidation of electron-rich aromatic compounds (Scheme 10). [35] Jiao and co-workers developed the azidation of skatole derivatives in the presence of alcohols to give dehydroindole derivatives (Scheme 10 A). [35a] Intramolecular attack of an alcohol to give indoline derivatives was also possible.H ao and co-workers reported the ortho azidation of anilines at room temperature (Scheme 10 B).…”
Section: Methodsmentioning
confidence: 99%
“…[34b] In 2014, two research groups reported the combination of copper catalysis with benziodoxolone 9 for the azidation of electron-rich aromatic compounds (Scheme 10). [35] Jiao and co-workers developed the azidation of skatole derivatives in the presence of alcohols to give dehydroindole derivatives (Scheme 10 A). [35a] Intramolecular attack of an alcohol to give indoline derivatives was also possible.H ao and co-workers reported the ortho azidation of anilines at room temperature (Scheme 10 B).…”
Section: Methodsmentioning
confidence: 99%
“…In recent years, hypervalent iodine reagents have emerged as environmentally friendly and efficient oxidizing reagents for various synthetically useful oxidative transformations 1. Particularly important are hypervalent iodine(III) compounds with iodinenitrogen bonds,2 such as azidoiodanes,2ae benziodazoles,2f, g amidobenziodoxoles,2j and iminoiodanes,2jo all of which are efficient reagents for CN bond forming reactions. Representative recent examples of synthetic applications of these reagents include direct azidation, amination, imidation, aziridination, metal‐catalyzed imidation, and CH insertion reactions 2.…”
Section: Methodsmentioning
confidence: 99%
“…Hao and co‐workers demonstrated in 2014 that Cu II can also be used to activate ortho ‐C–H bonds in anilines to give o ‐azido anilines . The difference from the protocol reported by Jiao and described above is that azidobenziodoxoles were used as the azide source instead of TMSN 3 , circumventing the need for an external oxidant.…”
Section: Base‐metal‐catalysed Azidation Reactionsmentioning
confidence: 99%